(untitled) (Bangladesh Journal of Medical Science, 2014)
Scedosporium apiospermum is a cosmopolitan mycotic agent with unique characteristics. This is a case of a 65-year-old immunocompetent patient who presented with shortness of breath and fever. Consolidation was observed in both lung fields on chest X-ray. A diagnosis of aspiration pneumonia was made. Extended-spectrum ?-lactamase (ESBL)-producing Klebsiella pneumoniae was identified from his tracheal aspirate and imipenem was administered. Initial blood cultures were negative but after 10 days on imipenem, Candida glabrata was isolated. Amphotericin B was added to the treatment regimen, but after a week on this antifungal, Scedosporium apiospermum was cultured from the blood. The patient succumbed to illness before a change in the antifungal regimen. The case highlights the unwelcome consequence of using a broad spectrum antibiotic and later a broad spectrum antifungal agent. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19154 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.326-328 Note: updated with minor changes on 20th June 2014. Last author added.